A Grid Middleware Framework Support for a Workflow Model Based on Virtualized Resources - Lee, Jinbock; Lee, Sangkeon; Choi, Jaeyoung (Future Application and Middleware Technology on e-Science, 2009)
Nowadays, the virtualization technologies are widely used to overcome the difficulty of managing Grid computing infrastructures. The virtual account and the virtual workspace are very optimistic to allocate Grid resources to specific user, but they lacks of capability of interaction between portal services and virtualized resources which required by Grid portal. The virtual application is fitted to wrap simple application as a Grid portal service, but integrating some applications to compose larger application service is difficult. In this paper, we present a Grid middleware framework which supports for a workflow model based on virtualized resources. Meta Services in the framework exposes workflow as a portal service and service call is converted different workflow according to parameter and workflow generated by the Meta Services is scheduled in a virtual cluster which configured by this framework. Because of virtual application service can be composed of workflow and service interface wraps the workflow providing a complex portal services composed by small application could effectively integrated to Grid portal and scheduled in virtual computing resources.